Identification of the Biomarkers and Pathological Process of Heterotopic Ossification: Weighted Gene Co-Expression Network Analysis - Wang, Shuang; Tian, Jun; Wang, Jianzhong; Liu, Sizhu; Ke, Lianwei; Shang, Chaojiang; Yang, Jichun; Wang, Lin (Frontiers in Endocrinology, 2020)
Heterotopic ossification (HO) is the formation of abnormal mature lamellar bone in extra-skeletal sites, including soft tissues and joints which resulting in high rates of disability. The understanding of HO mechanism is insufficient. The aim of our study was to explore biomarkers and pathological processes in HO+ samples. The gene expression profile GSE94683 was downloaded from the Gene Expression Omnibus database. 16 samples from 9 HO- and 7 HO+ subjects were analyzed. After data preprocessing, 3529 genes were obtained for weighted gene co-expression network analysis (WGCNA). Highly correlated genes were divided into 13 modules. Finally, the cyan and purple module was selected to be further researched. Gene ontology functional annotation and Kyoto Encyclopedia of Genes and Genomes pathway enrichment indicated that the cyan module was enriched in a variety of components including protein binding, membrane, nucleoplasm, cytosol, poly(A) RNA binding, biosynthesis of antibiotics, carbon metabolism, endocytosis, citrate cycle, metabolic pathways, etc. In addition, the purple module was enriched in cytosol, mitochondrion, protein binding, structural constituent of ribosome, rRNA processing, oxidative phosphorylation, ribosome, non-alcoholic fatty liver disease, etc. Finally, 10 hub genes in the cyan module (ACTR3, ARF4, PGRMC1, RPS23, M6PR, WDR12, SNAP23, ACTR2, SIAH1, GLMN) and 2 hub genes in the purple module (PSMA3, RPS27L) were identified. Hub genes were validated through Quantitative Real-time PCR. In summary, we find 12 hub genes in two modules are associated with HO. These hub genes could provide new biomarkers, therapeutic ideas and targets in HO.